Sustainable Food Production Through Vermicomposting – An EPS@ISEP 2021 Project - Mendes, Ana (2021)
The European Project Semester (EPS) is a multicultural, multidisciplinary teamwork and project-based learning framework offered to engineering, business and product design undergraduates by a network of European Higher Education institutions, including the Instituto Superior de Engenharia do Porto (ISEP). In the spring of 2021, five EPS@ISEP students from distinct countries and fields of study joined efforts to address the smart and sustainable food production issue. This paper reports their research and development of Wormify, a solution based on vermicomposting. The main goal of the project was to design, simulate, test and build a prototype following ethical and sustainable practices. Wormify aims to minimize the problem of feeding the growing global population, and to prevent food waste from going to landfills. These objectives were pursued by designing a smart modular system for urban rooftops or small balconies. Several modules can be connected to form a place for residents to meet and socialize. The smart system allows monitoring through an app/website. This paper presents the background studies, the concept and design, the development and final results.